Playing On: Re-staging the Passion after the Death of God - Klomp, Mirella (Theology in Practice, 2020)
In Playing On: Re-staging the Passion after the Death of God, Mirella Klomp shows how the Dutch playfully rediscover Christian heritage. Engaging theologically with a public Passion play, she demonstrates how precisely a production of Jesus' last hours carves out a new and unexpected space for God in a (post-)secular culture.; Readership: All interested in contemporary of Christian religion in contemporary Western cultures and anyone concerned with a quest for God in societies that can be seen as both 'post-secular' and 'post-Christian'.